find h(f(g(x)) f(x) = x^2 + 4 g(x) = [square root of 2x - 3 ] / x + 3 h(x) = 2x - 1 / x + 3 I have 4x + 1 / 2x + 3 Is this correct?

Follow Math Help Forum on Facebook and Google+

Hello, Originally Posted by moonman find h(f(g(x)) f(x) = x^2 + 4 g(x) = [square root of 2x - 3 ] / x + 3 h(x) = 2x - 1 / x + 3 I have 4x + 1 / 2x + 3 Is this correct? I think that you forgot to square (x+3) when computing f(g(x)) I get something like

Originally Posted by Moo Hello, I think that you forgot to square (x+3) when computing f(g(x)) I get something like I did indeed forget to square. Thank you my friend.

View Tag Cloud